Disruption of Pituitary Gonadotrope Activity in Male Rats After Short- or Long-Term High-Fat Diets Is Not Associated With Pituitary Inflammation - Garrel, Ghislaine; Rouch, Claude; L’Hôte, David; Tazi, Salma; Kassis, Nadim; Giton, Frank; Dairou, Julien; Dournaud, Pascal; Gressens, Pierre; Magnan, Christophe; Cruciani-Guglielmacci, Céline; Cohen-Tannoudji, Joëlle (Frontiers in Endocrinology, 2022)
Overnutrition is associated with the activation of inflammatory pathways in metabolically linked organs and an early hypothalamic inflammation is now known to disrupt the central control of metabolic function. Because we demonstrated that fatty acids (FA) target the pituitary and affect gonadotropin synthesis, we asked whether overnutrition induces pituitary inflammation that may contribute to obesity-associated disorders in the control of reproduction. We analyzed pituitary inflammation and hypothalamic-pituitary-testicular axis in male rats fed a short- (4 weeks) or long-term (20 weeks) high-fat diet. The effect of diet enrichment with the omega 3 polyunsaturated FA, DHA, was also analyzed. After only 4 weeks and before weight gain of rats, high-fat diet caused a significant decrease in pituitary gonadotropin and hypothalamic GnRH transcript levels despite unchanged testosterone and inhibin B levels. Contrasting with the hypothalamus, there was no concomitant increases in gene expression of pituitary inflammatory mediators and even a reduction of prototypical cytokines such as interleukin-1 beta and TNF-alpha No inflammation was still detected in the pituitary after 20 weeks although gonadotropin transcripts and circulating levels were still altered. Gonadotropins were the only pituitary hormones remaining affected at this stage of the regimen, underlying a differential susceptibility of pituitary lineages to metabolic disorders. DHA enrichment of the diet did not prevent alterations of gonadotrope activity due to either a long- or a short-term high-fat diet although it blocked early hypothalamic inflammation and attenuated several metabolic effects. Taken together, our findings suggest that high-fat diet-induced defects in gonadotrope activity in male rats occurred despite a lack of pituitary inflammation.